Community Participation In Village Development Planning In Nggembe Village, Bolo District, Bima Regency - Firmansyah Firmansyah; Arif Budiman; Salahuddin Salahuddin; Abdul Kadir (Badan Penerbit STIEPARI Press, 2024)
Regional autonomy is the implementation of territorial decentralization within the constitutional framework of Indonesia. As a result, regions have the rights, authority, and obligations to manage and govern their own household affairs in accordance with applicable laws and regulations. Democratization, empowerment, and public participation are the goals of the Regional Autonomy policy rollout in Indonesia. To achieve this, the government implements various decentralization policies. Provinces and districts are granted limited autonomy, while villages are given original autonomy. Both individuals and groups or communities engage in activities known as community participation, aiming to achieve communal goals by aligning their interests or relationships with organizations or the broader community. This study conducts qualitative descriptive research. The findings indicate that leadership, communication, and education influence community participation in Nggembe Village. The results show that the village head acts as a good leader; communication between the village government and the community is effective; and that the Nggembe Village population has a low level of education.